Partisipasi Masyarakat dalam Pembangunan Rumah Layak Huni di Kecamatan Talaga Jaya - Dini Ariska; Yanti Aneta; Alfiyah Agussalim (Transbahasa, 2025)
This study aims to analyze community participation in the construction of Livable Housing (RLH) in Talaga Jaya District, Gorontalo Regency. The research focuses on four main indicators of participation: decision-making, implementation, monitoring and evaluation, and utilization of results. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation. The informants consisted of village officials, BPD members, and RLH assistance recipients in three villages: Hutadaa, Bunggalo, and Buhu. The findings indicate that the level of community participation varies across the four indicators. Community members tend to be more active in the implementation and utilization stages, as seen in activities such as working together during construction and maintaining the completed houses. In contrast, participation in decision-making and evaluation remains relatively low due to the limited availability of dedicated forums that directly involve residents. Several factors influence participation levels, including education, economic conditions, access to information, and local cultural values. In conclusion, the success of the RLH program is strongly linked to active community involvement from the planning stage through to maintenance. Enhancing mechanisms that encourage inclusive participation is essential to ensure that housing development is more equitable, responsive to community needs, and sustainable over the long term.